On the Conflicting Estimations of Pigment Site Energies in Photosynthetic Complexes: A Case Study of the CP47 Complex - Reinot, Tonu; Chen, Jinhai H.; Kell, Adam; Jassas, Mahboobe; Robben, Kevin C.; Zazubovich, V.; Jankowiak, Ryszard (My University, 2016)
We focus on problems with elucidation of site energies (E-0(n)) for photosynthetic complexes (PSCs) in order to raise some genuine concern regarding the conflicting estimations propagating in the literature. As an example, we provide a stern assessment of the site energies extracted from fits to optical spectra of the widely studied CP47 antenna complex of photosystem II from spinach, though many general comments apply to other PSCs as well. Correct values of E-0(n) for chlorophyll (Chl) a in CP47 are essential for understanding its excitonic structure, population dynamics, and excitation energy pathway(s). To demonstrate this, we present a case study where simultaneous fits of multiple spectra (absorption, emission, circular dichroism, and nonresonant hole-burned spectra) show that several sets of parameters can fit the spectra very well. Importantly, we show that variable emission maxima (690-695 nm) and sample-dependent bleaching in nonresonant hole-burning spectra reported in literature could be explained, assuming that many previously studied CP47 samples were a mixture of intact and destabilized proteins. It appears that the destabilized subpopulation of CP47 complexes could feature a weakened hydrogen bond between the 13(1)-keto group of Chl29 and the PsbH protein subunit, though other possibilities cannot be entirely excluded, as discussed in this work. Possible implications of our findings are briefly discussed.
Citation: Reinot, T., Chen, J. H., Kell, A., Jassas, M., Robben, K. C., Zazubovich, V., & Jankowiak, R. (2016). On the Conflicting Estimations of Pigment Site Energies in Photosynthetic Complexes: A Case Study of the CP47 Complex. Analytical Chemistry Insights, 11, 35-48. doi:10.4137/aci.s32151
Keywords: Cp47; Photosynthesis; Redfield; Simplex; Chl Site Energies; Evolving Photosystem-Ii